Sistema que facilita la autonomía de los estudiantes de pregrado en entornos virtuales de educación universitaria. (2020)
Purpose - The purpose of this project is to increase the autonomy of undergraduate students who take classes virtually through a platform that encourages interaction, collaboration and motivation among users. Currently, new technologies have emerged as support elements within the learning process, even creating new learning methods such as e-learning. These new ways of learning are consolidated as strategies that can solve current problems in education, such as physical barriers and global access to knowledge. However, due to the little change that education has had and the lack of adaptation processes, students and teachers have had a hard time adapting and using these new technologies. Therefore, this project investigates the main problems of virtual education, such as the lack of autonomy and engagement in platforms, to generate a system, using virtual reality, that creates an interactive, collaborative and gamification-based ecosystem for the future of education...Curve. Design/methodology/approach - The project was divided into 2 stages. During the first stage, a theoretical framework, interviews with professors and a focus group with university students were carried out to determine the main problems of virtual education and establish the focus of the research. Observations and analysis of a virtual class and a classroom lesson were also made to compare them and determine what were the benefits of each one, in order to apply them to the final solution. In the second stage, the scrum methodology (Denning, S., 2011) was used to make the minimum viable product of 2 prototypes: a web platform and a virtual reality interactive space. To evaluate these prototypes, usability tests were performed and autonomy was measured with the parameters of the IMI - Intrinsic Motivation Inventory - (Self Determination Theory, nd) using questionnaires with a Likert scale.